Papers from the first European Workshop on Technological & Security Issues in Digital Rights Management (EuDiRights '06) - Yagüe, Mariemma (Online information review, 2007)
A selection of papers examining issues arising from the need to balance fair use and individual rights to information on the Web, with the rights of content providers.